Impact of metabolizing enzymes on drug response of endocrine therapy in breast cancer. (May 2013) - Saladores, Pilar H; Precht, Jana C; Schroth, Werner; Brauch, Hiltrud; Schwab, Matthias
Estrogen-receptor positive breast cancer accounts for 75% of diagnosed breast cancers worldwide. There are currently two major options for adjuvant treatment: tamoxifen and aromatase inhibitors. Variability in metabolizing enzymes determines their pharmacokinetic profile, possibly affecting treatment response. Therefore, prediction of therapy outcome based on genotypes would enable a more personalized medicine approach, providing optimal therapy for each patient. In this review, the authors will discuss the current evidence on the most important metabolizing enzymes in endocrine therapy, with a special focus on CYP2D6 and its role in tamoxifen metabolism.